Plasma β-amyloid 1–42 reference values in cognitively normal subjects - Zecca, Chiara; Tortelli, Rosanna; Panza, Francesco; Arcuti, Simona; Piccininni, Marco; Capozzo, Rosa; Barulli, Maria Rosaria; Barone, Roberta; Cardinali, Roberta; Abbrescia, Daniela; Seripa, Davide; Brescia, Vincenzo; et al. (Journal of the neurological sciences, 2018)
In clinical practice, the use of plasma β-Amyloid1-42 (Aβ ) as biomarker for Alzheimer's disease is largely limited by the absence of reference values. The aim of this study was to evaluate Aβ plasma concentrations in cognitively normal subjects and to propose reference values. Plasma samples were obtained from 245 subjects, with a wide age-range (19-89 years), enrolled at the Unit of Laboratory Medicine of the "Azienda Ospedaliera Cardinale G. Panico" (younger subjects) and from a population-based study on aging (GreatAGE study) (older subjects). Three different age-groups were established: young (≤ 34), adult (35 ≤ age ≤ 64) and old (>64). The Innogenetics Elisa kit for plasma Aβ was used for the analysis. The mean (SD) concentration of plasma Aβ was 17.65 (5.71) pg/mL. A positive trend was found in Aβ levels across the three age groups (p < .0001): young subjects showed values of Aβ significantly lower than the adult group (p < .0001) and than the old one (p < .0001 overall); no significant differences were found between the adult and the old groups (p = 1.0000). For the entire cohort the lower limit of 90% Reference Interval, double-sided, was 8.12 pg/mL (95% CI 6.77-9.45) and the upper limit was 29.00 pg/mL (95% CI 27.01-31.00). The present study proposes reference values for plasma Aβ . Nevertheless, further studies are needed to confirm these results and corroborate the use of these reference values in clinical practice.